Bridging the gap: understanding vaccination awareness and attitudes in healthcare students of the United Arab Emirates. - Adra, Saryia; Taha, Fatima; Raza, Hareem; Bilalaga, Sarah Juman; Al Moukdad, Almuzaffar Mustafa; Mahfouz, Mohamad; Zibdeh, Ali Banan; Barqawi, Hiba Jawdat; Abu-Gharbieh, Eman (Pharmacy Practice (1886-3655))
Background: Healthcare students (HCS) are at an elevated risk of infection and potential sources of infection for patients. This study focuses on HCSs in the United Arab Emirates (UAE) regarding their vaccination status, awareness, and attitudes. The lack of standardized vaccination policies among UAE medical universities and the recent global emphasis on HCSs' vaccination highlight the importance of this research. Methods: A cross-sectional, self-administered questionnaire, targeting current healthcare students in the UAE was conducted. A minimum sample size of 400 was calculated, and data were collected between March and May 2023. Statistical analysis including descriptive and inferential statistics were conducted. Results: Most of the participants received their childhood vaccination and some adult vaccines. Despite 97.3% claiming awareness of the importance of HCSs' vaccination, the average knowledge score was 8.5 ± 1.8 (score ranged from 0 to 13). Medical students had slightly lower knowledge scores compared to other healthcare majors. 75.9% received information on the required vaccinations before clinical training. There was a significant relationship between receiving information and awareness of the need for specific vaccinations (p<0.001). 56.0% checked their titres prior to clinical training, mainly due to training requirements (51.8%). Barriers to vaccination included vaccine availability and low perceived risk. Conclusion: This study underscores the gap between healthcare students' perceived and actual knowledge of the required vaccinations; highlighting the need for educational initiatives and clear vaccination information. Healthcare educational institutes play a crucial role in ensuring vaccination knowledge and practices of their students meet the recommended standards.